Mobilizing the psychology evidence base for the treatment of pediatric chronic pain: The development, implementation, and impact of the Comfort Ability Program. Issue 4 (16th June 2020) - Coakley, Rachael; Bujoreanu, Simona
Abstract: Over the past 20 years, our knowledge regarding evidence‐based psychological interventions for pediatric chronic pain has dramatically increased. Unfortunately, access to evidence‐based pain management interventions remains a challenge for many children and adolescents who suffer with persistent pain. Reducing patient burden and system‐level barriers to care are a central target of clinical innovations in pain treatment intervention. Psychological interventions are also increasingly focused on reducing biomedical biases that may inhibit attainment of services. While there are many new psychological interventions across an array of delivery platforms, few interventions have been systematically disseminated. This paper will highlight the translational research procedures that have informed the development and dissemination of the Comfort Ability Program (CAP), an interactive group‐based intervention teaching adolescents and their parents evidence‐based strategies to manage chronic or persistent pain. Now in its fifth year of dissemination, CAP has a demonstrated record of success with cross‐institutional implementation and sustainability at 18 hospitals across three countries. This paper reviews six dynamic and iterative phases of development, based on the Graham et al knowledge‐to‐action cycle (2006),  that have guided the implementation and dissemination research for this program. The phases of CAP development include the following: (a) identifying knowledge and clinical gaps in care, (b) generating knowledge assets and implementation procedures, (c) evaluating clinical outcomes and system‐level processes, (d) developing and testing dissemination procedures, (e) expanding partnerships and monitoring knowledge use, and (f) sustaining knowledge use and continued innovation. This paper targets primarily health professionals and administrators and secondarily caregivers and the public at large.